Kegagalan Coretax Memicu Wacana Publik, Mengikis Kontrak Sosial dan Kepercayaan Wajib Pajak - Sony Erstiawan, Martinus (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
The implementation of the core tax administration sistem (Core Tax Administration Sistem or Coretax) in early 2025, which was expected to modernise tax services, instead sparked a wave of public criticism due to various fatal technical obstacles. The dysfunction of this sistem not only hampered administration but also gave rise to discourse on distrust of state budget management. This study aims to analyse in depth how the failure to implement Coretax has eroded public trust and damaged the fiscal social contract between taxpayers and the state. The research method uses a qualitative approach with a Critical Discourse Analysis perspective based on Norman Fairclough's model. Data was collected through netnography from public comments and interactions on social media, then analysed through three dimensions: text (micro), discourse practice (meso), and social practice (macro). The findings show that public discourse is not merely technical complaints, but a form of symbolic resistance. At the micro level, sistem dysfunction is interpreted as evidence of incompetence and alleged budget irregularities. At the meso level, the public mobilises collective memory related to past government project failures to validate their distrust. At the macro level, this signifies a violation of the principle of reciprocity, whereby the state is perceived as demanding tax compliance without providing adequate services, thereby triggering a crisis of legitimacy. The implications of this study emphasise that digital transformation of the public sector requires transparency and accountability; failure to respond to this crisis has the potential to significantly reduce voluntary tax compliance.